2016
DOI: 10.1111/jbi.12831
|View full text |Cite
|
Sign up to set email alerts
|

There is more to the picture than meets the eye: adaptation for crypsis blurs phylogeographical structure in a lizard

Abstract: Aim We examined dorsal coloration in and genetic relationships among Iberian populations of the lizard Psammodromus algirus to determine the extent to which the current distribution of phenotypic variation is correlated with phylogeographical history or local environmental conditions. Location Iberian Peninsula, western Palaearctic. MethodsWe sequenced mitochondrial DNA (ND4 and adjacent tRNAs genes) in 36 populations, and seven microsatellite loci in eight representative populations. In 23 populations, lizard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 58 publications
3
37
0
Order By: Relevance
“…Only a previous study reported the amount of water loss at low body temperature (~24°C) throughout a day from a single locality (Ferreira et al , ). The populations studied here (see below) all belong to the same clade and show both little genetic differentiation and high gene flow (Verdú‐Ricoy et al , ; Díaz et al , ). Consequently, we would expect to attribute variability among populations to acclimation to local conditions (i.e.…”
Section: Introductionmentioning
confidence: 98%
“…Only a previous study reported the amount of water loss at low body temperature (~24°C) throughout a day from a single locality (Ferreira et al , ). The populations studied here (see below) all belong to the same clade and show both little genetic differentiation and high gene flow (Verdú‐Ricoy et al , ; Díaz et al , ). Consequently, we would expect to attribute variability among populations to acclimation to local conditions (i.e.…”
Section: Introductionmentioning
confidence: 98%
“…We used genotyping by sequencing (GBS; Elshire et al, ) and combined ROA and CIOA to explore how the fixation of ancestral genetic variation and genetic innovation underlie convergent local adaptation. To do so, we used as model species the most abundant and widespread lizard in the Mediterranean region of the Iberian Peninsula: the large Psammodromus Psammodromus algirus (Díaz et al, ; Figure ). This species shows consistent genetic and phenotypic divergence associated with environmental heterogeneity across its distribution range.…”
Section: Introductionmentioning
confidence: 99%
“…This species shows consistent genetic and phenotypic divergence associated with environmental heterogeneity across its distribution range. The northwest part of its range is more humid and temperate than the southeast, and this is mirrored by broad changes in the vegetation patterns, with forests dominating in the west and more open spaces in the east (Díaz et al, ). The genetic diversity of P. algirus is structured in two mtDNA lineages, eastern and western, separated ca.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations